The Closing of the Door of Ijtihad and the Application of the Law - Frank E. Vogel (International Institute of Islamic Thought, 1993)
This panel's center of gravity is Islamic legal theory and doctrine, particularly usul alfiqh. In this mom are many of the West's leading scholars in this field. This puts me out of step, for my work leads me to study fiqh and usul alfiqh chiefly from the viewpoint of their application, an approach that is the result of spending several years in Saudi Arabia studying the role of fiqh and the ulema in the Islamic legal system. I wish to submit, however, that there are a number of doctrinal problems to which a study of the law's application and practice or, in other words, a study of the legal system, stands to contribute a great deal. The closing of the door of ijtihad, which I intend to discuss, is such an issue. But first let me make some general points to support the general suggestion I have just made. In western studies of fiqh, we have often omitted, justifiably or not, any consideration of the law's application. Among the valid justifications for doing so is the very vastness of the doctrinal corpus. Another is that to get basic data on the law's historical application is far more difficult than fvding its black-letter doctrine. Other justifications are more questionable. For one, we have often made certain assumptions, which-stating them with due exaggeration-hold that Islamic law, since it became stagnant at an early period, was usually ignod in practice. As a d t of this, it is often maintained, fiqh retreated into the ideal world of scholarship while the application of the law fell under the sway of arbitrary and despotic rulers. Approaching the law with such an impression, however much in the background, scholars of Islamic law have, not surprisingly, spent little time on its application. This last justification for ignoring the law's application is now, I believe, rapidly eroding due to the efforts of scholars on many different fronts. Some, notably Professor Hallaq, are at work countering the exaggerated idea of the "closing of the door of ijtihad," a phrase used to convey the idea that fiqh became utterly stultified at an early stage. Other scholars ate examining late Shari'ah court records and legal documents ...